Peran Konten Dakwah Tiktok pada Akun @Hananattakistory dalam Meningkatkan Pemahaman Agama Islam Mahasiswa PAI UIN Mataram Angkatan 2022 - Yana Hendriani; Akhmad Asyari; Erlan Muliadi (Lisyabab : Jurnal Studi Islam dan Sosial, 2026)
The rapid growth of social media has transformed the methods of Islamic preaching (da'wah), particularly through TikTok, a platform widely used by young people. Although TikTok is often perceived as an entertainment medium that may have negative influences, it also offers significant opportunities as an effective digital da'wah platform for disseminating Islamic values. This study aims to describe the forms and content of da'wah messages presented on the TikTok account @hananattakistory and to analyze its role in enhancing the Islamic religious understanding of students in the Islamic Education (PAI) Department at the State Islamic University of Mataram, Class of 2022. The research employed a qualitative descriptive approach. Data were collected through observations of the da'wah content uploaded on the @hananattakistory account, interviews with PAI students from the 2022 cohort who actively use TikTok, and documentation. Data analysis was conducted using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The validity of the data was ensured through source, method, and time triangulation. The findings reveal that the da'wah content on @hananattakistory contains messages related to aqidah (faith), akhlaq (morality), and sharia (Islamic law), delivered through motivational messages, inspirational stories, advice, prayers, and invitations to hijrah using simple and easily understandable language. The content contributes to improving students’ religious understanding in cognitive, affective, and behavioral aspects. Students gained broader religious knowledge, stronger spiritual motivation, and more positive behavioral changes in their daily lives. However, its effectiveness is still influenced by the limited duration of videos and distractions from other content on TikTok.